The Effect Of Work Motivation, Competence And Compensation On Employee Spirit And Performance At Regional Office II Of The National Civil Service Agency In Surabaya - Pudjowati, Juliani; Susi Tri Wahyuni; Endang Siswati; Mochammad Balafif; Winarno (International Journal of Science, Technology & Management, 2022)
This study aims to examine and analyze the effect of Work Motivation, Competence, and Compensation on Spirit of Work and Employee Performance, as well as the influence of Spirit of Work on Employee Performance at Regional Office II of the National Civil Service Agency in Surabaya. The samples in this study were taken as many as 85 samples, namely 85 employees at Regional Office II of the National Civil Service Agency in Surabaya. Data analysis techniques using path analysis with SPSS software version 22. The conclusions obtained from this study are: (1) Work Motivation has a significant effect on Spirit of Work; (2) Competence has a significant effect on Spirit of Work; (3) Compensation has a significant effect on Spirit of Work; (4) Work Motivation has not significant effect on Employee Performance; (5) Competence has a significant effect on employee performance; (6) Compensation has not significant effect on employee performance; and (7) Work Spirit has a significant effect on Employee Performance at Regional Office II of the National Civil Service Agency in Surabaya.